The right to remain silent / Mary Hamim - Hamim, Mary (Faculty of Law, 1986)
The so-called right to silence ia a two-fold : in relation to the pre-trial stage (out-of-court) silence, where it means that the accused is entitled to abstain from making any statement or comment when interrogated by the police or other investigating authority. In relation to the trial stage (in-court) silence, the right to silence means that the prosecution have the onus of establishing his guilt, that he can decline to give evidence and that the prosecution may not comment on his so doing. An accused person who raises a plea of alibi for the first time does, however run serious risk. In such cases, the judge may, in the summing up (if it a jury trial) invite the jury to talk into consideration the ommission of the accused to disclose his defence at the preliminary enquiry in the Magistrate's court. It would however be a misdirection for the judge to infer or to invite the jury as the case may be to infer guilt by reason of such omission on the part of the accused.'*' In this respect, the law in Malaysia follows the English law as enunciated in various cases decided there. 2